Measuring library service quality and students’ satisfaction using structural equation modeling: A case study at UniSZA Library / Nurliana Yaacob - Yaacob, Nurliana (Bachelor of Science (Hons.) Statistics, 2015)
Measuring students’ satisfaction is important in terms of survival of an academic library. The primary aims of this paper are to determine the relationship between library services and students’ satisfaction and to identify the factors that influence the overall students’ satisfaction. This study was carried out at UniSZA Gong Badak Campus Library. This study involved 250 of respondents by using stratified random sampling. Data was collected by distributing a questionnaire to users of the library, those who visited to the library during a particular period. Structural Equation Modeling (SEM) approach is used to investigate the correlational relationships and causal effects among constructs. The results revealed that there is a positive relationship between library services and students’ satisfaction. Moreover, the study found that printed publication, environment, electronic resources, staff and facilities have a significant influence on students’ satisfaction. Collection of printed publication affects students’ satisfaction most profoundly. According to averaged mean values, students most satisfied with the library environment (M=7.137) followed by facilities (M=6.995), electronic resources (M=6.705), staff (M=6.691) and lastly printed publication (M=6.493).